Cult Film Stardom
XII, 288 p.
Keywords: The term 'cult film star' has been employed in popular journalistic writing for the last 25 years, but what makes cult stars distinct from other film stars has rarely been addressed. This collection explores the processes through which film stars/actors become associated with the cult label, from Bill Murray to Ruth Gordon and Ingrid Pitt.